On some spaces via topological ideals - Boonpok Chawalit (Open Mathematics, 2023)
Our main purpose is to introduce and investigate the concepts of some forms of spaces via topological ideals. Some characterizations of some forms of spaces via topological ideals are established. Moreover, several properties of ⋆\star -monotonically normal ideal topological spaces are considered.